THE DEVELOPMENT OF SCIENCE PROCESS SKILLSBASED ASSESSMENT ON MATERIAL FACTORS INFLUENCE THE RATE OFREACTION - ricka prasdiantika; nina kadaritna; noor fadiawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
This study aims to develop scienceprocess skills (SPS) based assessmenton material influence ofthe rate of reaction.The research methodused is theResearchand Development (RD).The results of this assessment, the development of the 15 multiple choice questions on the grounds, and 8 essay questions that measure indicators of cognitive products, and indicator SPS students who presented using macroscopic representation, submicroscopic representation, and symbolic.Results from the limited  testing it is known that SPSbased assessmentis in accordancewith thecurriculum of the SK-KD is the  percentage of 95.20%, is in accordance with the indicator SPS is the percentage 98.18%, has a very highlevel oflegibilityto the percentage of 86.56%, and has a very highlevel of interesting with thepercentage of88.33%. Based on theresponsesof teachers, SPS based assessmentis feasible for students tested.Keywords: assessment, reaction rate, scienceprocess skills